Synthesis and Characterization of Ni(II) and Cd(II) Complexes of 4-(4-Nitrophenylazo)-1H-pyrazole-3,5-diamine and 4-(4-Methylphenylazo)-1H-pyrazole-3,5-diamine - Adiguzel, Ragip; Esener, Hasan; Ergin, Zuhal; Aktan, Ebru; Turan, Nevin; Sekerci, Memet (Asian Journal of Chemistry, 2011)
In this study, the diazotized p-nitroaniline and p-methylaniline were coupled with malononitrile. The ring closure reaction of the obtained products with hydrazine monohydrate yielded 4-(4-methylphenylazo)-1H-pyrazole-3,5-diamine (L-1) and 4-(4-nitrophenylazo)-1H-pyrazole-3,5-diamine (L-2). The structure of the ligands has been elucidated by spectroscopic analyses. Then, novel Ni(II) and Cd(II) complexes of the ligands have been synthesized and the structures of these complexes determined by elemental analysis, spectrometric and TGA/DTA methods, molar conductance and magnetic susceptibility measurements. All the complexes were monomeric and diamagnetic. From the elemental analyses and mass spectra data, the complexes were proposed to the formulae [Ni-2(L-1)(2)(OH)(2)]center dot 2Cl center dot 8.5H(2)O, [Cd-2(L-1)(2)(OH)(2)]center dot 2Cl center dot DMF center dot 3H(2)O, [Ni(L-2)(2)]center dot 2Cl center dot 2DMF center dot 7H(2)O and [Cd-2(L-2)(2)(OH)(2)(H2O)(4)]center dot 2Cl center dot 1.5H(2)O. For the Cd(L-2) complex octahedral geometry was proposed, but the Ni(L-1), Ni(L-2) and Cd(L-1) complexes show four coordinated structure. The Ni(L-1), Cd(L-1) and Cd(L-2) complexes were found to be dinuclear. On the other hand the Ni(L-2) complex was found to be mononuclear. All the complexes were found to be (1:2) electrolytes.
Keywords: 4-(4-Nitrophenylazo)-1H-pyrazole-3,5-diamine and Metal complexes; 4-(4-Methylphenylazo)-1H-pyrazole-3,5-diamine and Metal complexes; Azodyes complexes